Diverse Outreach of Macroprudential Policy Effect on Household and Non-Financial Corporate Loan: An Indication of Macroprudential Policy Leak? - Khoirul Sukma; Akhmad Syakir Kurnia (Faculty of Economic and Business, 2022)
Despite increasing awareness of the importance of countercyclical policies to overcome financial system instability, the potential leak of such policies comes to attention due to economic agents' risk-taking behavior. This paper aims to investigate the potential leaks of the policy. Using the Estimator General Method of Moments-difference (GMM-diff), we found evidence that macroprudential policies are less functional in controlling non-financial firms' credit growth than household credit growth. The result amplifies hesitation about the effectiveness of macroprudential policy caused by potential leaks coming from non-financial firms' risk-taking behavior. We also found that macroprudential policy in developing countries is less effective than in developed countries. Hence, the financial stability goal cannot rely solely on macroprudential policy. Instead, it needs support from other mutual policies, such as the capital control policy and transparent regulatory boundaries, to prevent partial risk shift from regulated financial institutions to unregulated, prevalent in the less developed financial system.JEL Classification: E42, E44, E52, E58